Penerapan Metode Waterfall dalam Sistem Informasi Cuti Kepegawaian Madrasah Istiqlal - Badrul, Mohammad; Janah, Luthfiyah Nuur (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Human resources in a company organization are very important to support the progress and quality of the company in achieving its goals. One of the keys to the success of an organization is employees, who have an important role in an organization, therefore human resource management in an organization is carried out properly in order to be able to achieve the shared goals of the organization. The administrative process for employee data that is currently running at Madrasah Istiqlal Jakarta is still being done manually, one of which is applying for employee leave. This manual system has many shortcomings, namely the use of a long time, incomplete reports required, and more prone to errors. The process of collecting personnel data manually will cause the available data to be incomplete or missing and take a long time. Therefore, a personnel information system is needed to overcome these problems. A good Personnel System will produce precise and accurate data so that it greatly influences the course of decision making. The waterfall method has a high speed of adaptation, can be made quickly and also because the waterfall method is suitable for software products whose needs are clear at the beginning, so there are minimal errors. The result of this research is a personnel information system that can assist employees in receiving information with an integrated database